KRITIK HARALD MOTZKI TERHADAP KLASIFIKASI MODEL PEMIKIRAN HADIS HERBERT BERG - Ahmad Ramzy Amiruddin; Muhammad Alfatih Suryadilaga (Faculty of Ushuluddin UIN Syarif Hidayatullah Jakarta, 2021)
There are four classifications of hadith scholars measured by how skeptical they are of the authenticity of the hadith, namely Early Western Scepticism, Reaction Against Scepticism, Middle Ground, and Renewed Scepticism. Of the four classifications, Berg divides them into two groups, namely those who are skeptical and non-skeptical. In response to this, Harald Motzki specifically criticized Berg's classification. The data source that used is based on the article